Regulating Information or Allowing Deception? Pharmaceutical Sales Visits in Canada, France, and the United States. Issue 4 (2016) - Habibi, Roojin; Guénette, Line; Lexchin, Joel; Reynolds, Ellen; Wiktorowicz, Mary; Mintzes, Barbara
Abstract : Diverse legal and regulatory measures are used internationally to control the information provided during pharmaceutical sales visits. Little is known about the comparative effectiveness of these measures however. We analyzed the perceptions of regulators, pharmaceutical industry officials, health professionals, and consumer respondents concerning these approaches in Canada, France, and the United States using an empirical realist interests-based approach. Interviews focused on the aims and effectiveness of regulation, barriers and enablers to regulation and suggestions for improvement. An alignment was found in North America regulator and industry respondents' satisfaction with the status quo and their view that further intervention is unfeasible and unnecessary. Health professionals generally expressed a lack of confidence in the impact of regulations on sales visit information while consumer advocates voiced their disappointment in both regulators and health professionals for their failure to counteract the influence of pharmaceutical marketing. Regulator and industry respondents in France differed from their North American counterparts in their willingness to increase and diversify the scope of regulatory interventions. As the first international comparison of regulatory experiences in this sector, the findings highlight the universal need for more focused and inclusive discussions among groups about how to tailor regulations to achieve public health goals.